The research of blast resistant of reinforcement concrete beams in concrete structures at off-site oil and gas plant - Al Jasmi, S.; Nur Farhayu, Ariffin; Seman, M. A. (Penerbit UMP, 2021)
In the recent decades, blasts and gas explosions at the off-site of oil and gas plants have increased leading to destruction of important concrete structures, essential equipment and loss of human life. In response, structural engineers have come up with different ways of reinforcing beams of concrete structures using fiber reinforced polymers composite materials to produce blast resistant structures to minimize the impact of the blast loads, due to their unique and individual characteristics like high flexural and shear strength. This paper seeks to research the dynamic behavior, response and performance of reinforce concrete beams strengthened with Carbon Fiber Reinforced Polymer composites when subjected to blast loading. The study aims at proposing a design model of strengthening reinforce concrete beams with Carbon Fiber Reinforced Polymer in supporting concrete structures at off-site oil and gas plants against hydrocarbon explosions. Carbon Fiber Reinforced Polymer composites exhibit higher modulus of elasticity, higher energy absorption capacity, resistant to all forms of alkali and higher tensile strength compared to all other fiber reinforced polymers reinforcements and therefore the need to assess its capacity in protecting concrete structures at oil and gas plants against dynamic loads. The research will be carried out through numerical analysis using the finite element analysis computer program, ANSYS.